2014
DOI: 10.1245/s10434-014-3886-0
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive Diagnosis and Evaluation of Curative Surgery for Gastric Cancer by Using NMR-based Metabolomic Profiling

Abstract: An urinary metabolomics approach may be useful for the effective diagnosis of GC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
94
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(102 citation statements)
references
References 37 publications
7
94
1
Order By: Relevance
“…Some studies reported that caffeine inhibited colon cancer cell proliferation and reduced colorectal cancer risk 17,18 . Decreased hypoxanthine level was detected in the urine of patients with Non-Hodgkin lymphoma 19 , and the same trend of reduced level was observed in gastric cancer patients compared to normal individuals 20 . Hypoxanthine level showed reduction in the serum of advanced rectal cancer patients when it was compared between different stages of tumor progression 21 , which is consistent with our findings.…”
Section: Discussionsupporting
confidence: 55%
“…Some studies reported that caffeine inhibited colon cancer cell proliferation and reduced colorectal cancer risk 17,18 . Decreased hypoxanthine level was detected in the urine of patients with Non-Hodgkin lymphoma 19 , and the same trend of reduced level was observed in gastric cancer patients compared to normal individuals 20 . Hypoxanthine level showed reduction in the serum of advanced rectal cancer patients when it was compared between different stages of tumor progression 21 , which is consistent with our findings.…”
Section: Discussionsupporting
confidence: 55%
“…4-hydroxyphenylacetate, alanine, phenylacetylglycine, mannitol, glycolate, and arginine levels were significantly correlated with cancer T stage. Together with hypoxanthine level, the above mentioned metabolites were tended toward control after surgical treatment [32] . In a study by Chen et al [33] , urinary lactic acid, arginine, leucine, isoleucine and valine were significantly higher, while citric acid, histidine, methionine, serine, aspartate, malic acid, and succinate were remarkably lower in the gastric cancer patients vs controls.…”
Section: Urinary Metabolomics In Gi Cancersmentioning
confidence: 98%
“…In addition, the urinary valine and isoleucine levels were lower in advanced stages compared to early-stages of cancer [33] . Another study also showed that urinary metabolomics could effectively differentiate gastric cancer patients from controls [34] ; however, the metabolites which were distinctive, were different than previously mentioned studies [32,33] , suggesting complexity in interpreting metabolomics results.…”
Section: Urinary Metabolomics In Gi Cancersmentioning
confidence: 99%
“…NMR analytics have been used for biomarker detection in humans in several tumor entities other than PCa (Table 2): non-small-cell lung cancer (Doskocz et al, 2015), oral squamous cell carcinoma (OSCC) , gastric cancer (Jung et al, 2014), myeloma (Lodi et al, 2013), pancreatic ductal adenocarcinoma (Davis et al, 2013), lung cancer (Carrola et al, 2011), and BCa (Bansal et al, 2013).…”
Section: Prostate Cancermentioning
confidence: 99%